PENENTUAN SISWA PENERIMA BANTUAN PENDIDIKAN MENGGUNAKAN METODE AHP DAN SAW - Rita Sari Dewi; Ilka Zufria; M Fakhriza (JISTech (Journal of Islamic Science and Technology), 2022)
In the process of determining student beneficiaries using the manual method, it can affect time efficiency and data accuracy. By using a systematic calculation using a decision support system (DSS) that combines expert methods and SAW the resulting data can be used as an alternative to determine students who receive assistance to produce accurate data. In this case, the decision support system uses criteria, namely final semester grades, parental income, certificates, number of dependents and smart indonesia cards. This system is built on a web-based basis using the PHP programming language and Mysql database. The final result of this system can display ranking data and a combination of two methods. The resulting data can be printed in the form of a report. The resulting report can be used as a recommendation in the decision-making process regarding students who are entitled to receive educational assistance.